DINAMIKA KEPENTINGAN PARA AKTOR DALAM OPERASIONAL PT SORIKMAS MINING - , adelita lubis, Dr. Eric Hiariej, M.Phil ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Operating the company in the protected forest and national park, in fact it is not be the interest which prior by community and the local government always correlated with the environmental problems. It can be shown in research case of PT Sorikmas Mining in Mandailing Natal regency. Operational region of the company which located at national park region has been obtained massive the exploitation not only by media but also by environmental observer. Nevertheless this exploration news is actually different with the communityâs aspiration to the company. The most interest delivered by the community refers to economic problems. These economic problems actually are the most struggled by the local community such as job vacancy availability, land properties value, and custom land properties value. But, in some village which located near by the operational region of the company, the interest of environmental problem has already existed of main interest delivered by the local community. On other hand the interest delivered by the local government has not been correlated with the environmental problem, the dominant interest delivered by the local government is given the authority to the local government. The aims of the research are to analyze what kind of interests which delivered by the local government, community and PT Sorikmas Mining and how the using of power and resources belong to the actors in reaching to their goals. Correlate to the aim of the research, so the question of this research are âwhat kind of the interests delivered by the local government, community and PT Sorikmas Mining, and how the role of these actors using their power and resources own to reach their interests, and describe how the dispute among these actors recently occurred. The theory and the concept used to answer these questions are, approach basis on empowerment in political economy, environmental ethic and sustainable development, whereas to answer this research, the researcher using qualitative method with collecting data technique through interview, observation and then analyze the conclusion of these data. The result of these research are the most interest delivered by the community are not correlate with the environmental problem. Various action has been under taken by the community to reach their interest, but recently that interest (economic interest and environmental interest) has not been clearly further action from the company